High-Throughput Indirect Monitoring of torc1 Activation Using the Ptoman-G Plasmid in Yeast - Martinez-Fernandez, C; Kessi-Perez, E; Gomez-Luna, M (Bio-protocol LLC, 2025)
The target of rapamycin complex 1 (TORC1) is a highly conserved protein complex whose primary function is to link nutrient availability to cell growth in eukaryotes, particularly nitrogen sources. It was originally identified during the screening of Saccharomyces cerevisiae strains resistant to rapamycin treatment. For its part, S. cerevisiae is well known for being a key model organism in biological research and an essential microorganism for the fermentation of food and beverages. This yeast is widely distributed in nature, with domesticated and wild strains existing. However, little is known about what effects domestication has had on its different phenotypes; for example, how nitrogen sources are sensed for TORC1 activation and what impact domestication has had on TORC1 activation are questions that still have no complete answer. To study the genetic basis of TORC1 activation associated with domestication through approaches such as quantitative trait loci (QTL) mapping or genome-wide association studies (GWAS), and more generally for any study requiring TORC1 activity as a readout for a large number of individuals, it is necessary to have a high-throughput methodology that allows monitoring the activation of this pathway in numerous yeast strains. In this context, the present protocol was designed to assess phenotypical differences in TORC1 activation using a new reporter plasmid, the pTOMAN-G plasmid, specifically designed to monitor TORC1 activation. As a proof of concept, this methodology allowed phenotyping a large population of yeast strains derived from the 1002 Yeast Genomes Project, the most complete catalog of genetic variation in yeasts. This protocol proved to be an efficient alternative to assess TORC1 pathway activation compared to techniques based on immunoblot detection, which, although effective, are considerably more laborious. Briefly, the protocol involves the design and construction of the pTOMAN-G plasmid, which carries a construct containing the firefly luciferase gene (Luc) under the control of the TORC1-regulated RPL26A gene promoter (PRPL26A). The protocol then details the process for selecting subgroups of yeasts based on their ability to grow under nutrient-limited conditions, using proline as the sole nitrogen source. These yeasts are then transformed with the TOMAN-G plasmid, using two alternative transformation methods. Finally, those yeasts that emit luminescence are selected, whose phenotype for TORC1 activation is measured by a nitrogen-upshift experiment in microculture. This approach, using the pTOMAN-G plasmid, offers a rapid and consistent method for assessing TORC1 signaling pathway activation in a large number of yeast strains, highlighting its usefulness to study the activation of the TORC1 pathway and the domestication process associated with it. In the future, a redesign of the plasmid could extend its use as a reporter tool to monitor the activation of the TORC1 pathway, or other pathways, in other yeast species. ©: © 2025 The Authors.